Black carp PRMT6 inhibits TBK1-IRF3/7 signaling during the antiviral innate immune activation. Issue 93 (October 2019) - Jiang, Yuanyuan; Liu, Liqun; Yang, Shisi; Cao, Yingyi; Song, Xuejiao; Xiao, Jun; Feng, Hao
Abstract: Protein arginine methylation is a prevalent posttranslational modification and protein arginine methyltransferases 6 (PRMT6) has been identified as a suppressor of TBK1/IRF3 in human and mammals. To explore the role of PRMT6 in teleost fish, PRMT6 homologue of black carp ( Mylopharyngodon piceus ) has been cloned and characterized in this study. Black carp PRMT6 (bcPRMT6) transcription in host cells varies in response to different stimuli and bcPRMT6 migrates around 43 kDa in the immunoblot assay. Like its mammalian counterpart, bcPRMT6 has been identified to distribute majorly in the nucleus through the immunofluorescent staining assay. bcPRMT6 shows little interferon (IFN) promoter-inducing activity in the reporter assay and bcPRMT6 shows no antiviral activity against either grass carp reovirus (GCRV) or spring viremia of carp virus (SVCV) in plaque assay. When co-expressed with bcPRMT6, the IFN promoter-inducing abilities of black carp TBK1 (bcTBK1) and IRF3/7 (bcIRF3/7) are fiercely attenuated. Accordingly, bcTBK1-mediated antiviral activity in EPC cells is obviously dampened by bcPRMT6. The interaction between bcPRMT6 and bcIRF3/7 has been identified by co-immunoprecipitation assay; however, no direct association between bcPRMT6 and bcTBK1 has been detected. Taken together, our data elucidates for the first time in teleost fish that PRMT6 suppresses TBK1-IRF3/7 signaling during host antiviral innate immune activation. Highlights: bcPRMT6 suppresses bcTBK1 and bcIRF3/7 mediated IFN production. bcPRMT6 inhibits bcTBK1 mediated antiviral activity. bcPRMT6 interacts with bcIRF3/7, but not with bcTBK1.